2019
DOI: 10.1096/fj.201801583rr
|View full text |Cite
|
Sign up to set email alerts
|

AMPK‐mediated degradation of Nav1.5 through autophagy

Abstract: The voltage‐gated cardiac sodium channel, Nav1.5, is the key component that controls cardiac excitative electrical impulse and propagation. However, the dynamic alterations of Nav1.5 during cardiac ischemia and reperfusion (I/R) are seldom reported. We found that the protein levels of rat cardiac Nav1.5 were significantly decreased in response to cardiac I/R injury. By simulating I/R injury in cells through activating AMPK by glucose deprivation, AMPK activator treatment, or hypoxia and reoxygenation (H/R), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
2
9
1
Order By: Relevance
“…The FAT10 protein is not unique in regards to the regulation of Nav1.5 ubiquitination, as several proteins have been demonstrated to participate in this process, such as UBC9 25 , UBR3, and UBR6 26 . Furthermore, under ischemia or hypoxia, the UBS and autophagic activities were increased 7,27 , which was potentially responsible for the decreased Nav1.5 protein expression 5,24 However, the degradation of Nav1.5 could partially but not totally be rescued by the increased FAT10 expression under the conduction of ischemia by antagonizing Nav1.5 ubiquitination, demonstrating a cardioprotective effect of FAT10. These results might explain the increased FAT10 expression and decreased Nav1.5 expression under ischemic/hypoxia conditions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The FAT10 protein is not unique in regards to the regulation of Nav1.5 ubiquitination, as several proteins have been demonstrated to participate in this process, such as UBC9 25 , UBR3, and UBR6 26 . Furthermore, under ischemia or hypoxia, the UBS and autophagic activities were increased 7,27 , which was potentially responsible for the decreased Nav1.5 protein expression 5,24 However, the degradation of Nav1.5 could partially but not totally be rescued by the increased FAT10 expression under the conduction of ischemia by antagonizing Nav1.5 ubiquitination, demonstrating a cardioprotective effect of FAT10. These results might explain the increased FAT10 expression and decreased Nav1.5 expression under ischemic/hypoxia conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, we found that FAT10 expression was increased, while that of Nav1.5 was decreased under hypoxic conditions, and several factors may underlie this result. First, the degradation of Nav1.5 is regulated by complex molecular mechanisms, such as ubiquitination 5 and autophagy 24 . In the present study, FAT10 overexpression stabilized the Nav1.5 protein by regulating its ubiquitination.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that AMPK interacts with and phosphorylated CFTR to negatively regulate CFTR function (34,36,37). Additionally, AMPK interacts with and phosphorylates Na V 1.5 to regulate the interaction of Na V 1.5 with LC3 that is important for autophagic degradation (35). Considering that AMPK interacts with TRPM8 via the cytoplasmic C-terminus in a protein complex, additional studies are needed to determine whether and how AMPK phosphorylates TRPM8 at the C-terminus to modulate TRPM8 function.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK interacts with ion channels, including sodium channel Na V 1.5 and the cystic fibrosis transmembrane conductance regulator (CFTR), forming a protein complex (34)(35)(36)(37). Thus, we aimed to determine whether TRPM8 directly interacts with AMPK to promote AMPK activation and phosphorylation.…”
Section: Trpm8-ampk Interaction Leads To Ampk Activation To Enhance Cmentioning
confidence: 99%
“…SCN5A alterations, either up-or downregulation, are known to cause arrhythmias, and SCN5A is downregulated in ischemic cardiomyopathy (27)(28)(29). Nevertheless, the mechanisms whereby ischemia causes a reduction in SCN5A have not been fully explored but include mRNA destabilization (9,27).…”
Section: Discussionmentioning
confidence: 99%